An effective routing scheme of sparse wireless sensor networks - Chao SONG; Yingfeng ZHENG; Wenbin ZHAO (Dianxin kexue)
Mobile agent node has become the most efficiency way of data collection in sparse wireless sensor networks，because the distance of the nodes is too far. However，the mobile agent node could not access all the nodes to gather the data in a routing travel because of energy-constrained. In order to make the energy-constrained mobile agent node obtain the minimum total route，an effective routing scheme of energy-constrained mobile agent node in sparse wireless sensor networks was presented. The mathematic model of the route of mobile agent node was built firstly，and then the whole wireless sensor network was split into different subsets according to the energy of the mobile agent node. Then the shortest routes were computed by adopting simulated annealing of traveling salesman problem. Finally，the obtained total route of sub-routes was the optimal route. The analysis results of simulation and performance show that the total route of the presented scheme is close to the ideal situation along with the increase of the number of nodes and the raise of the energy of mobile agent node. So the presented scheme is very effective in the practice and is propitious to popularize.